2013
DOI: 10.1159/000346818
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use of Older Adults: A Mini-Review

Abstract: Background: Maintaining social relationships has been defined as a core element of aging well. With a considerable amount of older adults living alone, social media provides the possibility to engage in meaningful social contact, e.g. by joining online social networks and online discussion forums. Objective: The review encompasses current knowledge of prerequisites in social media use of older adults such as functional capacity, information and communications technology-related knowledge, and favorable attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
251
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(273 citation statements)
references
References 22 publications
12
251
2
8
Order By: Relevance
“…Furthermore, having specific knowledge is essential for the use of social media (21). Leist priate attitudes toward social media is necessary for the elderly to use social networks (22). The present study also indicated that the elderly used the Internet and social networks to have access to different information; however, they do not trust all received information.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, having specific knowledge is essential for the use of social media (21). Leist priate attitudes toward social media is necessary for the elderly to use social networks (22). The present study also indicated that the elderly used the Internet and social networks to have access to different information; however, they do not trust all received information.…”
Section: Discussionmentioning
confidence: 58%
“…Most older individuals use the internet to follow news and search for information (23). Similarly, Leist (2013) believes that the potentials of social networks can be employed to search and distribute health-related information on various diseases and treatments. This can have a positive impact on improving the elderlys' quality of life; however, the potential risk is that the shared information may contain inaccurate or even harmful details, especially concerning chronic and life-threatening conditions (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Canada and the USA, there appears to be a dramatic drop in Internet use among adults beyond 75 years old, even as usage among adults over 65 years continues to increase (Smith 2014;Statistics Canada 2011Zickuhr and Madden 2012). This decrease has been credited to lower income and decreased access to broadband service among adults 75 years and older, in addition to attitudes surrounding its utility and privacy, difficulty learning the technologies, and physical and/or cognitive impediments (Lee, Chen, and Hewitt 2011;Leist 2013). Usage of social media follows this trend (Dewing 2010).…”
Section: Social Media: Inclusive Tools For Change?mentioning
confidence: 99%
“…Google and Google Scholar were also searched to capture gray literature, popular or lay resources, and because they serve as simple, single points of entry to begin a search on a complex topic (Asher, Duke, and Wilson 2013). Finally, we examined citations of the literature discovered in our search, including those of literature reviews by Nef et al (2013) and Leist (2013). The reviewed literature then formed the basis for the following theoretical discussion on the conceptual links between ageism, senior citizenship, advocacy, and social media.…”
mentioning
confidence: 99%